Pengembangan Sistem Penasehat Akademik (SIPEKAD) Menggunakan Metode User Centered Design - Gunadi; Kudadiri, Parlindungan; Agustin; Hamdani; Susanti (SOTVI - Society of Visual Informatics, 2024)
STMIK Amik Riau is the first computer college in Riau Province. As the first and focused on the field of computerization, all activities carried out, whether related to work or services to students, should be computerized and mobile based. One of the services that is a problem in this research is the Academic Advisory (PA) service which is still carried out conventionally. Various problems that occur include failure to input student Study Plan Cards (KRS) into the feeder system by the Higher Education Data Base (PDPT) due to late submission, difficulty meeting lecturers for consultation due to lecturers' busy schedules, guidance times are relatively fast so students cannot convey complaints. in the lecture process as well as PA consultation sheets which are easily damaged and lost. The many problems that exist conventionally give rise to the desire to integrate all existing problems into a system that can be accessed by students online. In building a system that integrates all existing problems, the author uses a system development process in the form of the User Centered Design method. The application of this method is focused on a system built to achieve research objectives and in accordance with the wishes of the user. The results that have been achieved are implemented directly with students and provide positive feedback because of the ease with which students can meet PA lecturers to consult on problems during the lecture process as well as the ease with which lecturers can monitor the entire history of their PA students.